Effect of Diquat on gut health: molecular mechanisms, toxic effects, and protective strategies - Cheng He; Guorong Cai; Yingmao Jia; Rong Jiang; Xiaolan Wei; Ning Tao (Frontiers in Pharmacology)
Diquat is a widely used bipyridyl herbicide that is extensively applied in agricultural production and water management due to its high efficacy in weed control. However, its environmental persistence and the toxic effects it induces have raised widespread concern. Studies show that Diquat primarily enters the body through the digestive tract, leading to poisoning. The core mechanism of its toxicity involves reactive oxygen species (ROS)-induced oxidative stress, which not only directly damages the intestinal barrier function but also exacerbates inflammation and systemic toxicity by disrupting the balance of the gut microbiota and the normal production of metabolic products. This review systematically summarizes the physicochemical properties of Diquat, with a focus on analyzing the mechanisms by which it damages the gut tissue structure, barrier function, and microbiota after digestive tract exposure. The aim is to provide theoretical support for a deeper understanding of Diquat’s toxic mechanisms and its digestive tract-centered toxic characteristics, laying a scientific foundation for the development of effective interventions and protective strategies against its toxicity.